The influence of Youtube advertising towards brand image - Eva Paiqhatul Himah; Terra Saptina Maulani (Universitas Negeri Padang, 2021)
The purpose of this research is to find out how much influence Youtube Advertising has on Brand Image. The sampling method used was probability sampling technique consisting of 100 respondents. The method of analysis in this study uses descriptive and verification analysis consisting of simple linear regression analysis, coefficient of determination and hypothesis testing used to measure the magnitude of the effect of product design and Youtube Advertising on brand image. The results of the research conclude that overall Youtube Advertising is in a pretty good category and Brand Image is in a pretty good category. The results also concluded that Youtube Advertising has an effect on the Brand Image of Indoeskrim Nusantara Colossal Advertising.